An Efficient Full-Wave Electromagnetic Analysis for Capacitive Body-Coupled Communication - Muhammad Irfan Kazim; Muhammad Imran Kazim; J. Jacob Wikner (International Journal of Antennas and Propagation)
Measured propagation loss for capacitive body-coupled communication (BCC) channel (1 MHz to 60 MHz) is limitedly available in the literature for distances longer than 50 cm. This is either because of experimental complexity to isolate the earth-ground or design complexity in realizing a reliable communication link to assess the performance limitations of capacitive BCC channel. Therefore, an alternate efficient full-wave electromagnetic (EM) simulation approach is presented to realistically analyze capacitive BCC, that is, the interaction of capacitive coupler, the human body, and the environment all together. The presented simulation approach is first evaluated for numerical/human body variation uncertainties and then validated with measurement results from literature, followed by the analysis of capacitive BCC channel for twenty different scenarios. The simulation results show that the vertical coupler configuration is less susceptible to physiological variations of underlying tissues compared to the horizontal coupler configuration. The propagation loss is less for arm positions when they are not touching the torso region irrespective of the communication distance. The propagation loss has also been explained for complex scenarios formed by the ground-plane and the material structures (metals or dielectrics) with the human body. The estimated propagation loss has been used to investigate the link-budget requirement for designing capacitive BCC system in CMOS sub-micron technologies.